Evaluation of interleukin‐6 and serotonin as biomarkers to predict response to fluoxetine. (27th March 2016) - Manoharan, Aarthi; Rajkumar, Ravi Philip; Shewade, Deepak Gopal; Sundaram, Rajan; Muthuramalingam, Avin; Paul, Abialbon
Abstract : Objective: Only 30% of major depressive disorder (MDD) patients achieve complete remission with a serotonergic antidepressant (selective serotonin reuptake inhibitor). We investigated the potential of serotonin (5‐HT) and interleukin‐6 (IL‐6) to serve as functional biomarkers of fluoxetine response. Methods: Serum IL‐6 and 5‐HT were measured in 73 MDD patients (39 responders and 34 non‐responders) pre‐ and 6 weeks post‐treatment and in 44 normal controls with ELISA. Fluoxetine and norfluoxetine were measured using LC MS/MS. Results: IL‐6 levels were significantly higher in MDD patients when compared with controls ( p < 0.01), and 5‐HT levels were significantly lower in non‐responders compared with controls ( p = 0.0131). Pre‐ and post‐treatment levels of both biomarkers individually and in combination did not significantly differ between responders and non‐responders. Area under the receiver operating characteristics curve for the biomarkers was 0.5. Significant correlation was seen between the percentage change in IL‐6 and percentage change in Hamilton Rating Scale for Depression score in responders. Fluoxetine and norfluoxetine concentrations were not significantly different in responders and non‐responders, and there was no correlation between fluoxetine concentrations and percentage reduction in 5‐HT from week 0 to 6. Conclusion: 5‐HT and IL‐6 may not serve as useful markers of response to fluoxetine because of inconsistent results across different studies. Copyright © 2016 John Wiley & Sons, Ltd.